Using pattern language for a single family house: teaching a beginning architecture design studio at Kabul University, Faculty of Engineering, Department of Architecture - Azizi, Hemayatullah (Kansas State University, 2011)
This thesis assesses concepts of architectural education both globally and regionally but ultimately presents a pedagogy aimed at the special needs of Afghan architectural education that will serve the needs of Afghan society. It is the author’s hope that this thesis may aptly establish the first steps for a renewed architectural education at Kabul University, Kabul, Afghanistan. The essence of this thesis presents a carefully reasoned and detailed educational strategy for teaching beginning architectural design. The new curriculum in the Department of Architecture at Kabul University requires new syllabi to achieve higher academic standards. The new design course syllabus should address the existing problems of Afghan society. This thesis begins by understanding the context and the current problems confronting the Kabul University Department of Architecture. It is by understanding these problems that I can begin to identify a solution. Understanding the Kabul Municipality rules and regulations, familiarity with beginning design terminology, a carefully stated and sequenced course description promoting gradual student improvement, understanding interrelationships between the interior spaces, environmental sustainable design, and finally introducing a new generation of conscientious architects to Afghan society are some of the main objectives for designing this course. Identifying the best strategy for teaching this course was a primary research question. Christopher Alexander’s great work, A Pattern Language inspired me to select it as the best methodology for my research. My early research focused upon the creation of a new syllabus for the first semester of architectural design at Kabul University. This new syllabus was launched during the first semester of 2009 in Kabul where I taught the new course alongside a junior Afghan faculty member. Establishing the new course materials for the first semester set the stage for my primary focus of this thesis. That is the creation of the second semester architectural design course using pattern language as my pedagogical framework. This pedagogy is fundamental for establishing architectural studies focused upon meaningful new academic criteria. The ultimate aim of my thesis is to lay the foundation stone for the reincarnation of Afghan architectural identity.
Keywords: Afghanistan; Architecture Education; Pattern Language; Kabul University; Architecture Design Studio; Architecture (0729)